2006
DOI: 10.1021/jf061417c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Disruption of Bovine Casein Micelles at Alkaline pH

Abstract: The disruption of casein micelles at alkaline pH was investigated using turbidity measurements. The rate and extent of disruption of casein micelles at alkaline pH (8.0-11.0) increased with pH. Furthermore, the extent of alkaline disruption increased with increasing temperature (5-40 degrees C). Preheating milk for 10 min at 90 degrees C did not influence the extent of alkaline disruption of casein micelles, suggesting that whey proteins do not influence the alkaline disruption process. Levels of ionic calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 30 publications
7
81
2
Order By: Relevance
“…Indeed, we observed between pH 6.7 and 10.8, a significant and similar increase in the negative charge of the caseins from −20 to −24 mV for both milks. This change of charge was also reported and discussed by Vaia et al [20]. The consequences of these charge changes could have resulted in some modifications in the protein-protein interactions in the casein micelles leading towards disruption.…”
Section: Changes In the State Of Ionisation Of Proteinssupporting
confidence: 74%
See 4 more Smart Citations
“…Indeed, we observed between pH 6.7 and 10.8, a significant and similar increase in the negative charge of the caseins from −20 to −24 mV for both milks. This change of charge was also reported and discussed by Vaia et al [20]. The consequences of these charge changes could have resulted in some modifications in the protein-protein interactions in the casein micelles leading towards disruption.…”
Section: Changes In the State Of Ionisation Of Proteinssupporting
confidence: 74%
“…This delay in the physico-chemical changes can be related to the concentrations of proteins especially caseins (about 35 and 25 g·kg −1 in cow and buffalo milks, respectively) and minerals especially Ca (65.2 and 33.1 mmol·L −1 in buffalo and cow milks, respectively) and Pi (32.7 and 20.8 mmol·L −1 in buffalo and cow milks, respectively) [1]. The first part of this interpretation concerning the dependence of alkalinisation process on protein contents is supported by the results of Vaia et al [20] who indicated that the disruption of casein micelles induced by alkalinisation was slower when the concentration of proteins increased.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations